Viabilidade da obtenção de quasicristais AlCuFe, com materiais reciclados, sem atmosfera controlada - Fonseca Júnior, Franklin Lacerda de Araújo (2024)
With the development of technology in recent years and the progress in researching new materials and processes, materials science becomes more and more important in technological innovation worldwide. Based on this premise, quasicrystalline alloys have reached an important role due to their atypical properties, which has led to an incentive in studies and research with the objective of analyzing the stability of this material under adverse conditions, thus developing new alloys, new techniques of production, use of new precursor materials, among others. Currently, due to scarcity and concern for the ecosystem, there is an intense need to reduce the impacts on the environment and society. Based on this assumption, In this work, a quasicrystalline Al-Cu-Fe alloy was developed from recycled precursors, with nominal composition Al62.2Cu25.5Fe12.3, using conventional casting without a controlled atmosphere as a method of obtaining, castings took place in loads of 150g. The formation of the icosahedral phase was followed by several analysis techniques. The results of x-ray diffraction and scanning electron microscopy demonstrated that the formation of the quasicrystalline phase occurred. The corrosion resistance properties of the alloys obtained showed that they have a corrosion potential close to that of materials such as stainless steel. Differential thermal analysis showed the formation peak of the quasicrystalline phase in both alloys produced. The methodology proved to be efficient for producing quasicrystalline alloys in comparison to techniques already proven to be used. It can be seen, therefore, that the new route for processing quasicrystalline materials proves to be an effective route, with excellent prospects in terms of larger-scale production.